Cross‐sectional survey study of primary care clinics on evidence‐based colorectal cancer screening intervention use. Issue 4 (16th November 2021) - Watanabe‐Galloway, Shinobu; Kim, Jungyoon; LaCrete, Frantzlee; Samson, Kaeli; Foster, Jason; Farazi, Paraskevi A.; LeVan, Tricia; Napit, Krishtee
Abstract: Purpose: The purpose of this study was to examine differences between urban and rural primary care clinics in the use of colorectal cancer (CRC) screening methods and evidence‐based interventions to promote CRC screening. Methods: This was a cross‐sectional survey of primary care clinics in Nebraska. Surveys in paper form were sent out and followed up with telephone interviews to nonrespondents. Of the 375 facilities, 263 (70.1%) responded to the survey. Findings: Over 30% of urban clinics indicated that 80% or more of their patients were meeting the CRC guidelines compared to 18.3% of rural clinics ( P = .03). Rural clinics were more likely than urban clinics to prefer the use of colonoscopy alone or in combination with stool tests ( P = .02). The most common interventions for CRC screening included one‐on‐one patient education and use of computer‐based pop‐ups to remind providers. Conclusions: In conclusion, we found some important differences between rural and urban primary care clinics in the implementation of CRC screening. Given that there is evidence for differences in preference for CRC screening methods (colonoscopy vs stool‐based tests) between rural and urban community members, it is important to assess the effectiveness of different types of CRC screening interventions by comparing rural and urban primary care clinic patient populations.